Molecular Prevalence of Babesiosis in Buffaloes of North Gujarat - Ganguly, Nabanita; Parsani, Husen R; Thakre, Bhupendrakumar J; Rathwa, Sawan D (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Babesiosis is a tick-borne disease caused by haemo-protozoan parasites of the genus Babesia with four main species, viz., Babesia  bigemina, Babesia bovis, Babesia major and Babesia divergens and is characterized by significant morbidity and mortality worldwide. The  present study was conducted to investigate the prevalence of B. bigemina in water buffaloes of North Gujarat. Ticks mostly present in  the study area are Rhiphicephalus (Boophilus) spp. and Hyalomma spp., etc. A total of 223 blood samples were drawn from buffaloes of  different age groups during October 2022 to September 2023 and analysed by microscopic and PCR techniques. The overall prevalence  of Babesia bigemina infection in buffaloes was 6.72 (15/223) % by conventional microscopic method and 9.86 (22/223) % by PCR. No  blood samples were found positive for other Babesia spp. by microscopic as well as by PCR based assay. Babesiosis was found to be more  common in age group of 1-3 years old followed by 3-5 and > 5 years old buffaloes, with calves below < 1 year showed the least infection.  Summer season had highest prevalence followed by monsoon and winter seasons. The haematological and biochemical parameters  were found to be non-significantly altered, except the levels of Hb, TEC, PCV, which were found to be significantly decreased and the  levels of WBC, granulocytes were found significantly elevated.
Keywords: Babesiosis; Buffalo; Molecular detection; North Gujarat; Prevalence